Existence of Positive Solutions of a Singular Nonlinear Boundary Value Problem. (18th August 2010) - Ma Ma, Ruyun Ruyun; Li Li, Jiemei Jiemei
Abstract : We are concerned with the existence of positive solutions of singular second-order boundary value problem u ″ ( t ) + f ( t, u ( t ) ) = 0, t ∈ ( 0, 1 ), u ( 0 ) = u ( 1 ) = 0, which is not necessarily linearizable. Here, nonlinearity f is allowed to have singularities at t = 0, 1 . The proof of our main result is based upon topological degree theory and global bifurcation techniques.